Naples: the City of the Sun and Parthenope: the role of astronomy, mythology and Pythagoras in the urban planning of Neapolis - Scafetta, Nicola (FedOA - Federico II University Press, 2024)
This essay delves into the most intimate secret of Naples through an archaeoastronomical inquiry. It demonstrates that religious and philosophical motivations were central to the urban planning of its ancient Greek centre, Neapolis, constructed in the 6th- 5th centuries BC by Cumaeans and other Greek colonists. The design of the city's streets and its distinctive geographical-astronomical orientation evoked the cults of Apollo (the Greek Sun-god) and Parthenope (the local Numen, who reminds the mythical Sibyl of Cumae) on solstices and equinoxes. Neapolis' street grid was also inspired by Pythagorean cosmology, as it was designed with golden ratio and decagonal proportions. These elements combined to make Neapolis a perfect microcosm, or better yet, a temple-city centred on the cult of the Sun and Parthenope. Finally, the city’s religious traditions likely increased the public impact of the martyrdom of Saint Januarius, facilitating the Christianization of Naples in the 4th century AD. Naples’ ancient streets, culture, and Cathedral still preserve the legacy of Neapolis' solar traditions in their geometries, symbols, hymns, sweets, mosaics, and relics.